The site-specific distribution of atheromatous plaques in the coronary arteries - Wasilewski, Jarosław; Czaja-Ziółkowska, Monika Zofia; Gąsior, Mariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2023)
The etiology of atherosclerosis is still unknown, but there are several hypotheses trying to explain this complex disease. Most consider atherosclerosis as a cholesterol storage disease. However, hypercholesterolemia is not a cause but a risk factor. Besides, like other well-known systemic risk factors, it does not explain the uneven distribution of atheromatous plaques in the vasculature. Atherosclerotic lesions develop mainly at vulnerable “risk points” of the arterial wall such as curvatures and near side branches, and predominantly in the left anterior descending (LAD), while the left circumflex (LCx) artery is relatively spared. Furthermore, atheromatous plaques are present mainly in the proximal segments in the LAD and LCx, in contrast to the right coronary artery (RCA), where plaques are more evenly distributed. The hemodynamic theory explains to some extent the distribution of atherosclerotic lesions and considers atherosclerosis as a reactive biological response of endothelial cells to wall shear stress. In this review, we discuss the interplay of concentration of low-density lipoproteins at the luminal surface and local hemodynamic forces (disturbed flow) that reduce wall shear stress in the process of plaque formation. Moreover, we present the distribution of atheromatous plaques in the coronary arteries in autopsy studies and imaging methods such as cardiac computed tomography angiography and invasive coronary angiography.